Status of endangered large prey predators following civil unrest in a biodiversity hotspot of India - Vaibhav Chandra Mathur; Jayanta Kumar Bora; Jyotishman Deka; Deb Ranjan Laha; Keshab Gogoi; Qamar Qureshi; Ujjwal Kumar (Scientific Reports)
Abstract Biodiversity hotspots, often located in regions of armed conflict face severe threats. Manas National Park, at the confluence of Indo-Burma and Himalaya hotspots, suffered two decades of civil unrest (late 1980s to early 2000s), causing habitat destruction and wildlife declines, including local extinction of the greater one-horned rhinoceros and near-extirpation of swamp deer. Using elephant-back line transect distance sampling and camera trap-based spatially explicit capture-recapture in 2022 and 2023, we assessed post-conflict recovery of endangered prey-predator guilds. We recorded high densities of elephant (9.14 (SE 2.16) per km²), wild buffalo (4.47 (SE 1.51) per km²), and tiger (7.91 (SE 1.05) per 100 km²), while gaur, sambar, and barking deer showed stable densities compared to 2015 baselines. Rhinoceros and swamp deer populations grew significantly (17 (SE 3) and 17 (SE 1) % annually), while hog deer and wild pig populations declined sharply. Tiger poulation recovered, with 57 adults, establishing Manas as a source population for the transboundary landscape, while leopard maintained stable densities (4.77 (SE 0.80) per 100 km2. Integration of local stakeholders and digital tools like MSTrIPES improved monitoring efficiency. We recommend targeted augmentation programs for declining species, sustained habitat protection, and the use of elephant-back transects for accurate density estimation of ungulates and megaherbivores.